Principals’ Managerial Skills in Integrating Local Wisdom into School Culture and Character Education - Siti Nurjannah; Edi Chandra (BRIDGE : The Multidisciplinary Research Portal, 2025)
The integration of local wisdom into school culture has become an essential strategy for strengthening character education in increasingly globalized educational contexts. This study explores how principals’ managerial skills contribute to the effective integration of local wisdom values into school culture and their implications for student character development. Employing a qualitative case study design, data were collected through in-depth interviews, non-participant observations, questionnaires, and document analysis involving principals, teachers, students, and community stakeholders. Thematic analysis was applied to examine managerial practices across key functions, including planning, organizing, directing, and supervising. The findings indicate that principals with strong managerial leadership are able to align school vision and mission with local cultural values, facilitate teacher collaboration, adapt curriculum and extracurricular programs, and actively engage community participation. These practices support the institutionalization of local wisdom within daily school activities and learning processes. As a result, schools demonstrate notable improvements in student character indicators, particularly discipline, responsibility, respect, collaboration, and participation in cultural activities. However, the study also identifies persistent challenges, such as limited resources, uneven teacher commitment, and varying levels of stakeholder support, which require adaptive leadership and continuous evaluation. This study contributes to the educational leadership literature by providing empirical insights into the role of managerial leadership in sustaining culturally responsive school environments. The findings highlight the importance of strategic leadership, stakeholder engagement, and systematic monitoring in embedding local wisdom as a foundation for holistic character education across diverse school contexts.